RISK MANAGEMENT AND DISTRICT DEVELOPMENT INDEXES: A CASE APPROACH - Arroyo-González, Luis Nelson (2015)
Seventeen districts with a high recurrence of floods and landslides were identified during the period 1999-2009. For the purpose of this article, six districts were selected in order to show the discrepancies between the data collected and its eventual utility when this information was needed to be used to construct indicators and to analyze social and economic vulnerability via local and district human development indexes.